Surveillance of bloodstream infections in pediatric cancer centers - what have we learned and how do we move on? - Simon, Arne; Furtwängler, Rhoikos; Graf, Norbert; Laws, Hans Jürgen; Voigt, Sebastian; Piening, Brar; Geffers, Christine; Agyeman, Philipp; Ammann, Roland A. (German Medical Science GMS Publishing House, 2016)
Pediatric patients receiving conventional chemotherapy for malignant disease face an increased risk of bloodstream infection (BSI). Since BSI may represent an acute life-threatening event in patients with profound immunosuppression, and show further negative impact on quality of life and anticancer treatment, the prevention of BSI is of paramount importance to improve and guarantee patients' safety during intensive treatment. The great majority of all pediatric cancer patients (about 85%) have a long-term central venous access catheter in use (type Broviac or Port; CVAD). Referring to the current surveillance definitions a significant proportion of all BSI in pediatric patients with febrile neutropenia is categorized as CVAD- BSI. This state of the art review summarizes the epidemiology and the distinct pathogen profile of BSI in pediatric cancer patients from the perspective of infection surveillance. Problems in executing the current surveillance definition in this patient population are discussed and a new concept for the surveillance of BSI in pediatric cancer patients is outlined.